The Effect of Product Quality on Purchasing Decisions and Their Implications on the Relationship Equity of the Automotive Sector - Dudung Juhana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2018)
This research was conducted to empirically examine the effect of product quality on purchasing decisions and their implications for relationship equity in the Automotive sector in the city of Bandung. The research method uses a quantitative approach and uses consumer surveys. Sample respondents were 108 people using simple random sampling technique — data analysis with SPSS for Windows tools. The results of the study show that there is a significant effect of product quality on relationship equity, whether mediated by purchasing decisions or not mediated by purchasing decisions. The results of this study indicate that the impact of product quality on relationship equity is well mediated by purchasing decisions of 44.1%, while the influence of product quality on relationship equity is 29.3%. The results of the study show that with excellent product quality, it will be able to improve purchasing decisions with the support of relationship equity.